Hepatoprotective effects of Elaeagnus latifolia fruit extract against acetaminophen-induced hepatotoxicity in mice: Mechanistic insights - Narongsuk Munkong; Kingkarnonk Ruxsanawet; Varitha Ariyabukalakorn; Wirinya Mueangchang; Sarawut Sangkham; Pongsaton Silangirn; Arthid Thim-uam; Jarinyaporn Naowaboot; Nuntiya Somparn; Bhornprom Yoysungnoen (Journal of Functional Foods, 2024)
Elaeagnus latifolia fruit extract (EE) has been reported to contain antioxidant and anti-inflammatory phytochemicals. The present study aimed to examine the anti-hepatotoxic effects of EE in acetaminophen (APAP)-injected mice. Pretreatment with EE for 7 days in APAP mice showed significant reductions in the levels of AST and ALT and necrotic area, accompanied by decreases in liver oxidative stress, nitric oxide, and infiltrating inflammatory cells, compared to the APAP-only group. EE markedly down-regulated expression of CYP2E1, JNK, Bax, NOX subunit, and NF-κB target genes, and up-regulated expression of Bcl-2 and Nrf2 target genes in the livers. Furthermore, EE effectively lowered serum and hepatic lipids, and down-regulated expression of SREBP-1c/2 genes. EE was found to contain phenolic compounds, flavonoids, and proanthocyanidins. Therefore, mechanistic insights into EE's anti-hepatotoxic effects may be associated with preventing the abnormal expression of genes involved in toxic metabolite generation, hepatotoxic signaling, apoptosis, oxidative stress, inflammation, and lipid synthesis.